Oriental commerce, or, The East India trader's complete guide : containing a geographical and nautical description of the maritime parts of India, China, Japan, and neighbouring countries ... with an account of their respective commerce ... / originally compiled by William Milburn ... a careful digest ... with much additional and valuable matter by Thomas Thornton. - Milburn, William. (Tufts University. Tisch Library., 2015)
586 p., [21] folded leaves of plates : maps ; 26 cm.